PERISTIWA KOTO TUO LAUTAN API PADA MASA PEMERINTAHAN DARURAT REPUBLIK INDONESIA (PDRI), KECAMATAN HARAU, 10 JUNI 1949 - Renti, Siska Maya; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The formation of the Emergency Government of the Republic of Indonesia (PDRI) led by Mr. Syafruddin Prawiranegara who was in Bukittinggi in reaction to the Second Military Aggression launched by the Dutch on 19 December 1948 made the PDRI succeeded in continuing the leadership of the Republic of Indonesia by mobile, moving from one place to another to avoid the Dutch pursuit. In his pursuit of the founders of the PDRI, the Dutch got so much resistance from the people who were in the area they passed including in Nagari Koto Tuo who had to face the burning by the Dutch against their village. The purpose of this research is1) To know the condition of Koto Tuo before the event of Koto Tuo Lautan Api, 2) To know the background of the event of Koto Tuo Lautan Api, 3) To know the events of Koto Tuo Lautan Api, 4) To know the result of the Koto Tuo Events of the Flame of Fire. The research uses qualitative research methods with historical approach (History) and data collection techniques in the form of bibliography, documentation, observation and interview. The result of this research is the resistance made by Nagari Koto Tuo society to make the Dutch angry and burn almost all building in Nagari Koto Tuoas well as killing several warriors in Nagari. So great the sacrifices and struggles that have been passed by the heroes of the nation, thus we should as the next generation of the nation to always remember and appreciate the services of the heroes and not forget any historical events that occur in this country.Keywords: Koto Tuo Lake Fire, PDRI, Harau Districk